2017
DOI: 10.11606/issn.1678-4456.bjvras.2017.121241
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of viral diseases in donkeys (Equus asinus) in São Paulo State, Brazil

Abstract: Among the diseases that affect equines, viral diseases play an important role from a health and economic point of view, especially influenza, viral arteritis, herpes infections and vesicular stomatitis. In the Brazilian literature, there is little or no account of the occurrence of infectious diseases in donkeys. Given the importance of donkeys in different activities and the lack of information on infections that may occur in these animals, the aim of this study was to determine the frequency of anti-equine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Regarding the correlation between sex and disease, there were differences in results among different studies. Bolfa et al [69] suggested that males are more susceptible to infection by EHVs 1 and 4, while Lara et al [70] and Negussie et al [101] suggested a possible role of females in the "maintenance" of the disease in the herd, as they are more susceptible to EHV infection. In donkeys and mules, an infection with a gammaherpesviruses similar to Asinine herpesvirus type 5 (AHV-5), isolated from a pharynx swab of a donkey with neurological disease in Ontario, Canada have been reported [112].…”
Section: Equine Herpesvirusmentioning
confidence: 99%
“…Regarding the correlation between sex and disease, there were differences in results among different studies. Bolfa et al [69] suggested that males are more susceptible to infection by EHVs 1 and 4, while Lara et al [70] and Negussie et al [101] suggested a possible role of females in the "maintenance" of the disease in the herd, as they are more susceptible to EHV infection. In donkeys and mules, an infection with a gammaherpesviruses similar to Asinine herpesvirus type 5 (AHV-5), isolated from a pharynx swab of a donkey with neurological disease in Ontario, Canada have been reported [112].…”
Section: Equine Herpesvirusmentioning
confidence: 99%
“…In Brazil, a recent study demonstrated the frequency of antibodies to some equine diseases in donkeys in the state of São Paulo. Of the 85 serums evaluated, it was estimated that 50.6% exhibited antibodies against the H3N8 subtype of the influenza virus, 47% against the equine Herpesvirus, and 20% against the equine arteritis virus, demonstrating that these agents circulate among donkeys in the region and reiterating the importance of epidemiological monitoring of equids in Brazil [ 7 ].…”
Section: Relationship Between Disease Occurrence and Type Of Donkementioning
confidence: 99%
“…In this context, the investigation of diseases affecting donkeys and mules becomes important and gives rise to discussions on animal welfare and public health. This is demonstrated particularly in serological studies that show the participation of donkeys and mules in the epidemiological chain of reportable diseases [ 7 , 8 ]. It is furthermore important to highlight that cultural factors may influence the frequency of these diseases, affecting both animal and human health and welfare.…”
Section: Introductionmentioning
confidence: 99%
“…EHV-1 and EHV-4 are serologically identified in donkeys with the risk of spreading to neighboring countries. Natural occurrence and experimental infection with EHV-1 were reported in donkeys ( Lara et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%